Interactive Multimedia Based on Balinese Jejahitan Ethnomathematics Improves Learning Outcomes of Fourth Grade Elementary School Students - Ni Kadek Wina Indrasari; Gusti Ngurah Sastra Agustika; Adrianus I Wayan Ilia Yuda Sukmana (International Journal of Elementary Education, 2026)
The low mathematics learning outcomes of students remain a significant issue influenced by various factors, one of which is the limited use of interactive multimedia in the learning process. This study aims to analyze the design, validity, feasibility, and effectiveness of interactive multimedia based on Balinese Jejahitan ethnomathematics on the topic of plane geometry. This research employed a Research and Development (R&D) approach using the ADDIE model and involved fourth-grade elementary school students as the subjects of the trials. Data were collected through questionnaires and tests, with instruments consisting of expert validation sheets and multiple-choice tests. Data analysis was conducted using descriptive qualitative and quantitative methods, followed by inferential statistical analysis using a paired sample t-test. The results indicate that the developed multimedia has a very high level of validity and feasibility based on expert evaluations and student trials. Furthermore, the effectiveness test shows a significant improvement in students’ learning outcomes after the implementation of the interactive multimedia. In conclusion, interactive multimedia based on Balinese Jejahitan ethnomathematics is effective for use in mathematics learning. The findings imply that the integration of local cultural elements through interactive media can enhance student engagement and conceptual understanding in a more meaningful way.